2021
DOI: 10.1007/s00217-021-03911-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of aroma-active components in black teas produced by six Chinese tea cultivars in high-latitude region by GC–MS and GC–O analysis

Abstract: In this study, gas chromatography-mass spectrometry (GC-MS) and gas chromatography-olfactometry (GC-O) analysis was performed to figure out the characteristic aroma compounds of high-latitude black teas and select the suitable cultivar for producing high-aroma black tea. Sensory evaluation revealed that Jinxuan presented an obviously floral aroma and got the highest score, followed by Longjing Changye, Zhongcha 302, Yingshuang, Baihaozao and Huangshan Quntizhong. Furthermore, a total of 135 volatiles were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 47 publications
(52 reference statements)
1
4
0
Order By: Relevance
“…The detail of this factor was also further explored by other previous studies. For example, Jinxuan and other five kinds of tea cultivars were manufactured into black tea; subsequently, the detection results showed that the tea samples made from Jinxuan possessed a higher floral aroma, which is in concert with the previous finding that this tea cultivar is also suitable for floral-aroma type black tea processing [34]. It has been found that the floral odorants in different varieties of fresh tea leaves impact the aroma quality of processed tea as well as assist the assessment of cultivar processing-suitability [35].…”
Section: Discussionsupporting
confidence: 63%
“…The detail of this factor was also further explored by other previous studies. For example, Jinxuan and other five kinds of tea cultivars were manufactured into black tea; subsequently, the detection results showed that the tea samples made from Jinxuan possessed a higher floral aroma, which is in concert with the previous finding that this tea cultivar is also suitable for floral-aroma type black tea processing [34]. It has been found that the floral odorants in different varieties of fresh tea leaves impact the aroma quality of processed tea as well as assist the assessment of cultivar processing-suitability [35].…”
Section: Discussionsupporting
confidence: 63%
“…The Shandong tea‐growing area is located at a high latitude of 35° 35′ N–37° 9′ N with a relatively low mean annual temperature of 11–14 °C, a sufficient light resource of mean annual illumination of 2290–2890 h, and a relatively low mean annual rainfall of 550–950 mm. The special climate features of Shandong make an outstanding green tea characterized by a high and sharp aroma and a heavy and strong taste 10 . The chestnut‐like aroma is also considered an important indicator for excellent quality of Shandong green tea.…”
Section: Introductionmentioning
confidence: 99%
“…The special climate features of Shandong make an outstanding green tea characterized by a high and sharp aroma and a heavy and strong taste. 10 The chestnut-like aroma is also considered an important indicator for excellent quality of Shandong green tea. To our knowledge, the dynamic changes of volatile components in different process stages and the main formation stage of chestnut-like aroma has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Oolong tea made from the 'Huangdan' variety is famous for its strong aroma, while the 'Tieguanyin' variety has a more peaceful aroma. Wang Z Q et al (2015) found that the content of benzyl alcohol, phenylethanol, and phenylacetaldehyde in Huangdan black tea was higher than that in Tieguanyin black tea [39]. These studies suggest that the quality characteristics of the strong aroma of Huangdan oolong tea are related to the accumulation of VBs/VPs during manufacturing.…”
Section: Detection and Analysis Of Vbs/vps In Raw Oolong Teamentioning
confidence: 97%